The practical christology of Philoxenos of Mabbug - Michelson, David Allen (Oxford early Christian studies, 2014)
Map : Philoxenos of Malbbug : geographic extent of influence, late fifth to early sixth centuries A.D. -- Introduction : the world of Philoxenos of Mabbug--a practical context for understanding late-antique Christology -- Ordaining Satan : practical considerations in the divine Oikonomia -- In pursuit of divine knowledge : patristic sources of Philoxenos' theological epistemology -- Proof texts for the ineffable : on knowing Christ through Scripture -- "Though he cannot be eaten, we consume him" : Christological threats to liturgical practice -- Beginning the discipleship of Christ : theological conflict as ascesis and spiritual struggle -- Conclusion : Christological polemics in the context of spiritual practice